Percepția populației cu privire la grupurile sociale dezavantajate și formele de intervenție pentru incluziunea sociala finanțate din fondurile europene - Arpinte, Daniel (Calitatea Vieții, 2017)
The article aims to investigate the perception of adult population and of the social economy entities representatives on the implementation of the European funded projects, and to identify the population perception related to the support for social inclusion of vulnerable groups. Another objective is to investigate the perception of beneficiaries and those involved in EU funded projects implementation. The article use data coming from a survey carried out in 2013, with a representative sample for adult population, and a convenience sample for the representatives of the social economy entities. The results show that the adult population would rather support the infrastructure than those aiming at social inclusion for vulnerable groups. In case of the respondents in favour of social inclusion projects, there is a clear preference for those vulnerable which are not able on their own to overcome social exclusion. The opinion of the social economy representatives is clearly different, unconditionally supporting the social inclusion projects. In the case of the respondents which have been involved in the implementation of European funded project in the area of social economy, the opinion on program management, relevance and final results and impact, are rather negative.